A New Potential Cause in the Development of Toxic Anterior Segment Syndrome: Fibrin Glue - Selçuk Sızmaz; Cem Küçükerdönmez; Altuğ Çetinkaya; Yonca Aydın Akova (Türk Oftalmoloji Dergisi)
Objectives: To present a potential cause for toxic anterior segment syndrome (TASS). Materials and Methods: We report 4 cases of TASS that occurred following uneventful phacoemulsification and intraocular lens implantation. Results: The 4 cases were the first consecutive 2 cases of 2 different surgery days, 5 months apart. The most prominent sign of TASS was limbus-to-limbus corneal edema. Pain and/or intraocular pressure rise were also common. All surgical and presurgical procedures were checked after the first outbreak, whereas the second outbreak required further investigation. Fibrin glue remnants from preceding pterygium surgery with conjunctival autografting were found to be the potential cause. Despite intensive corticosteroid therapy, corneal edema did not resolve in 2 patients who underwent keratoplasty. Conclusion: TASS is a sight-threatening condition which requires thorough investigation for prevention of new cases. All steps must be carefully revised. (Turk J Ophthalmol 2014; 44: 280-3)